2006
DOI: 10.3346/jkms.2006.21.3.539
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Benign Paroxysmal Positional Vertigo in Korea: A Multicenter Study

Abstract: Benign paroxysmal positional vertigo (BPPV) is characterized by episodic vertigo and nystagmus provoked by head motions. To study the characteristics of BPPV in a large group of patients in Korea, we retrospectively analyzed clinical features of 1,692 patients (women: 1,146, 67.7%; men: 54.6, 32.3%; mean age: 54.8±14.0 yr), who had been diagnosed as BPPV by trained neuro-otologists Dizziness Clinics. The diagnosis of BPPV was based on typical nystagmus elicited by positioning maneuvers. Posterior semicircular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 23 publications
7
86
1
2
Order By: Relevance
“…* Lateral semicircular canal BPPV may spontaneously remit more quickly than other forms of BPPV. 72,184 There have also been several recent randomized controlled studies on both forms of lateral semicircular canal BPPV. 58,[196][197][198] Casani et al demonstrated the effectiveness of these 2 types of CRPs in treating the geotropic form of lateral semicircular canal BPPV.…”
Section: Lateral (Horizontal) Semicircular Canal Bppv Crp Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…* Lateral semicircular canal BPPV may spontaneously remit more quickly than other forms of BPPV. 72,184 There have also been several recent randomized controlled studies on both forms of lateral semicircular canal BPPV. 58,[196][197][198] Casani et al demonstrated the effectiveness of these 2 types of CRPs in treating the geotropic form of lateral semicircular canal BPPV.…”
Section: Lateral (Horizontal) Semicircular Canal Bppv Crp Treatmentsmentioning
confidence: 99%
“…Some authors have commented that lateral canal BPPV may be prone to more rapid spontaneous resolution than posterior canal BPPV. 72,184 One study of untreated patients (n = 34) with posterior canal BPPV determined a mean interval from onset of symptoms to spontaneous resolution to be about twice that of those patients with lateral canal BPPV (39 vs 16 days, respectively). 70 Although repositioning maneuvers have shown success in lateral canal BPPV, the available high-quality comparative data regarding treatment versus observation (eg, RCTs) are limited in this subtype of BPPV.…”
Section: Action Statement Profile For Statement 4cmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum slow-phase velocity among the BLT-responsive patients was higher than that of nonresponsive patients: 36.7 /sec versus 11.7 /sec, respectively, in the canalolithiasis type and 29. 4 /sec versus 8.6 /sec, respectively, in the cupulolithiasis type; these differences were statistically significant (Fig. 6).…”
Section: Comparison Of Remission Rates Between the Blt-responsive Andmentioning
confidence: 73%
“…The most common type of BPPV involves the posterior semicircular canal (PSC), but horizontal semicircular canal (HSC) BPPV accounts for about 6% to 40.5% of all patients presenting with BPPV. [1][2][3][4][5] The incidence of HSC-BPPV significantly decreases according to the duration of symptoms owing to a high spontaneous resolution rate. 5 In contrast to PSC-BPPV, HSC-BPPV nystagmus is induced by a quick turn of the head to the side while the patient is in a supine position and shows little change with repeated positioning.…”
Section: Introductionmentioning
confidence: 99%